Unlocking the potential of Rosmarinic acid: A review on extraction, isolation, quantification, pharmacokinetics and pharmacology - Haritha Harindranath; Aishwarya Susil; Rajeshwari S; Mahendran Sekar; B.R. Prashantha Kumar (Phytomedicine Plus)
Background: Rosmarinic acid (RA) is a polyphenol abundantly found in culinary herbs like Rosemary, sage, perilla, and Tulsi, and it has varied therapeutic potential. It is an ester of caffeic acid and 3,4—di hydroxyphenyl lactic acid. It's been used as a food supplement and in traditional medicines since immemorial. Objectives: To review RA's properties, sources, extraction methods, chemical structure, bioavailability, and diverse therapeutic applications such as antioxidant, anti-inflammatory, anticancer, neuroprotective, cardioprotective, and antimicrobial properties. Methods: A systematic data review was carried out focussing on literature from 2004 – 2024 in online databases from Google Scholar, PubMed, ScienceDirect, Web of Science, Researchgate, and Scopus. The articles were searched using “Rosmarinic acid”, “Cancer”, “in silico”, “in vivo”, “in vitro”, “diabetes”, and “therapeutic” as the keywords. Conclusion: This review provides deep insights into the research works carried out on RA's potential as a medicinal source. Advancement from normal traditional usage to modern-day therapeutic practices, RA has come a long way to help mankind with its unique characteristics. From anti-bacterial to anti-cancer remedies RA has proven its healing properties and still provides a scope to explore further.